A Research On Malaysian Corporate Websites To Study Their Web Based Business Activities - Thomas, Praji Sara (2005)
The scope of this research is to investigate and evaluate Malaysian Corporate websites quantitatively and qualitatively for their web business activities.The websites will be analyzed from four different sectors and similarities and difference of online behavior will be observed and studied.